2020
DOI: 10.1371/journal.pone.0231002
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome of multiple resistance donor plant Sinapis alba: An insight into SSRs, annotations and phylogenetics

Abstract: Background Sinapis alba is a wild member of the Brassicaceae family reported to possess genetic resistance against major biotic and abiotic stresses of oilseed brassicas. However, the resistance nature of S. alba was not exploited generously due to the unavailability of usable genome sequences in public databases. Therefore, the present study was conducted to assemble the first draft genome from raw whole genome shotgun sequences with annotation and develop simple sequence repeat markers for molecular genetics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…In the current study, Alternaria black spot disease infection was high on half of the tested cruciferous species, and we consider that this pathogen constitutes a direct threat to oilseed crops. Altered climatic conditions for plant growth due to global change and the growing population of the world reinforce the development of strategies for a sustainable agriculture and food system that ensure the efficient land use and high nutritional value of plants [43]. Thus, the knowledge of Alternaria black spot spread and plant vulnerability allows selection of more resistant species and cultivars, and this information is highly relevant for oilseed, intercrop, cover crop and green manure production, especially in sustainable farming systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, Alternaria black spot disease infection was high on half of the tested cruciferous species, and we consider that this pathogen constitutes a direct threat to oilseed crops. Altered climatic conditions for plant growth due to global change and the growing population of the world reinforce the development of strategies for a sustainable agriculture and food system that ensure the efficient land use and high nutritional value of plants [43]. Thus, the knowledge of Alternaria black spot spread and plant vulnerability allows selection of more resistant species and cultivars, and this information is highly relevant for oilseed, intercrop, cover crop and green manure production, especially in sustainable farming systems.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they have suggested that it might be a part of the S. alba-specific gene sequence. We have used this 288 bp sequence DNA sequence in the Basic Local Alignment Search Tool Nucleotide (BLASTN) with the S. alba draft genome assembly (Kumari et al, 2020a) and found three copies of approximately similar sequences in S. alba genome. Apart from this, we have studied the histology of physiologically mature seeds of both allohexaploids (yellow and mottled seeded).…”
Section: Discussionmentioning
confidence: 99%
“…The medicinal plant Isatis indigotica (2n = 14, Figure 2b,c ) shows resistance to diseases caused by bacteria and viruses (Kang et al ., 2020 ). White mustard ( Sinapis alba , 2n = 24) has yellow seeds, resistance to biotic and abiotic stresses, pod shatter resistance, and beneficial ingredients for humans (Kumari et al ., 2020 ). Some Brassicaceae species with insect resistance have also been identified, as reviewed in Herve ( 2018 ).…”
Section: Broadening the Genetic Diversity Of The Brassica Napus Gene Poolmentioning
confidence: 99%